Dental chews positively shift the oral microbiota of adult dogs. (29th March 2021) - Oba, Patrícia M; Carroll, Meredith Q; Alexander, Celeste; Somrak, Amy J; Keating, Stephanie C J; Sage, Adrianna M; Swanson, Kelly S
Abstract: Microbiota plays a prominent role in periodontal disease, but the canine oral microbiota and how dental chews may affect these populations have been poorly studied. We aimed to determine the differences in oral microbiota of adult dogs consuming dental chews compared with control dogs consuming only a diet. Twelve adult female beagle dogs (mean age = 5.31 ± 1.08 yr) were used in a replicated 4 × 4 Latin square design consisting of 28-d periods. Treatments ( n = 12/group) included: diet only (CT ); diet + Bones & Chews Dental Treats (BC ; Chewy, Inc., Dania Beach, FL); diet + Dr. Lyon's Grain-Free Dental Treats (DL ; Dr. Lyon's, LLC, Dania Beach, FL); and diet + Greenies Dental Treats (GR ; Mars Petcare US, Franklin, TN). Each day, one chew was provided 4 h after mealtime. On day 27, breath samples were analyzed for total volatile sulfur compound concentrations using a Halimeter. On day 0 of each period, teeth were cleaned by a veterinary dentist blinded to treatments. Teeth were scored for plaque, calculus, and gingivitis by the same veterinary dentist on day 28 of each period. After scoring, salivary (SAL ), subgingival (SUB ), and supragingival (SUP ) samples were collected for microbiota analysis using Illumina MiSeq. All data were analyzed using SAS (version 9.4) using the Mixed Models procedure, with P < 0.05 considered significant. All dogs consuming chews had lower calculus coverage and thickness, pocket depth and bleeding, plaque thickness, and halitosis compared with CT. In all sites of collection, CT dogs had a higher relative abundance of one or more potentially pathogenic bacteria ( Porphyromonas, Anaerovorax, Desulfomicrobium, Tannerella, and Treponema ) and lower relative abundance of one or more genera associated with oral health ( Neisseria, Corynebacterium, Capnocytophaga, Actinomyces, Lautropia, Bergeyella, and Moraxella ) than those fed chews. DL reduced Porphyromonas in SUP and SUB samples. DL and GR reduced Treponema in SUP samples. DL increased Corynebacterium in all sites of collection. BC increased Corynebacterium in SAL samples. DL and GR increased Neisseria in SAL samples. DL increased Actinomyces in the SUB sample. GR increased Actinomyces in SAL samples. Our results suggest that the dental chews tested in this study may aid in reducing periodontal disease risk in dogs by beneficially shifting the microbiota inhabiting plaque and saliva of a dog's oral cavity. These shifts occurred over a short period of time and were correlated with improved oral health scores.